Inhibitory effects of inhaled complex traditional Chinese medicine on early and late asthmatic responses induced by ovalbumin in sensitized guinea pigs - Gong Cheng-Chung; Chang Hung-Chou; Chen Ji-Liang; Mak Oi-Tong (BMC, 2011)
Abstract Background Many formulae of traditional Chinese medicines (TCMs) have been used for antiasthma treatment dating back many centuries. There is evidence to suggest that TCMs are effective as a cure for this allergenic disease administered via gastric tubes in animal studies; however, their efficacy, safety and side effects as an asthmatic therapy are still unclear. Methods In this study, guinea pigs sensitized with ovalbumin (OVA) were used as an animal model for asthma challenge, and the sensitization of animals by bronchial reactivity to methacholine (Mch) and the IgE concentration in the serum after OVA challenge were estimated. Complex traditional Chinese herbs (CTCM) were administered to the animals by nebulization, and the leukocytes were evaluated from bronchoalveolar lavage fluid (BALF). Results The results showed that inhalation of CTCM could abolish the increased lung resistance (13-fold increase) induced by challenge with OVA in the early asthmatic response (EAR), reducing to as low as baseline (1-fold). Moreover, our results indicated higher IgE levels (range, 78-83 ng/ml) in the serum of sensitized guinea pigs than in the unsensitized controls (0.9 ± 0.256 ng/ml). In addition, increased total leukocytes and higher levels of eosinophils and neutrophils were seen 6 hours after challenge, and the increased inflammatory cells were reduced by treatment with CTCM inhalation. The interleukin-5 (IL-5) level in BALF was also reduced by CTCM. Conclusion Our findings indicate a novel method of administering traditional Chinese medicines for asthma treatment in an animal model that may be more effective than traditional methods.